Terpenoids from Ainsliaea latifolia and their cytotoxic activities. Issue 3 (3rd March 2016) - Dong, Xue-Yun; Wang, Guo-Wei; Zhuo, Zhi-Guo; Lv, Chao; Fang, Xin; Shi, Zhi-Ran; Zeng, Ren-Tao; Shen, Yun-Heng; Zhang, Wei-Dong
Abstract : Two new compounds including one new sesquiterpenoid and one new monoterpenoid, together with 10 known compounds were isolated from the whole plants of Ainsliaea latifolia . The structures of these compounds were elucidated by analysis of spectroscopic data. All compounds were evaluated for their cytotoxic activities.